1982
DOI: 10.1108/eb026734
|View full text |Cite
|
Sign up to set email alerts
|

Humanities Scholars: Information Needs and Uses

Abstract: The literature of the information needs and uses of humanities scholars in universities is reviewed, using, in the main, material published from 1970 onwards. The areas covered include definitions of humanities, the way humanities scholars work and the materials of their research; secondary services; computers and new technology; the role of libraries and library services and comparisons between humanities and other disciplines. The review ends with a brief assessment of the state of the art; an outline of som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
137
1
12

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(156 citation statements)
references
References 18 publications
6
137
1
12
Order By: Relevance
“…Junto a esta característica aparecen otras también típicas de las disciplinas de humanidades (Stone, 1982;Watson-Boone, 1994), como que la colaboración sigue siendo inusual o la orientación regional y local de muchos trabajos, lo que suele traducirse en el hecho de que los autores tienden a publicar profusamente en otros idiomas diferentes al inglés. Los valores de obsolescencia son también los habituales en humanidades.…”
Section: Conclusionesunclassified
“…Junto a esta característica aparecen otras también típicas de las disciplinas de humanidades (Stone, 1982;Watson-Boone, 1994), como que la colaboración sigue siendo inusual o la orientación regional y local de muchos trabajos, lo que suele traducirse en el hecho de que los autores tienden a publicar profusamente en otros idiomas diferentes al inglés. Los valores de obsolescencia son también los habituales en humanidades.…”
Section: Conclusionesunclassified
“…Um den FachwissenschaftlerInnen im Bereich der Geisteswissenschaften geeignete Werkzeuge und Informationsinfrastrukturen zur Verfügung stellen zu können, ist es wichtig, ihre Ziele und Vorgehensweisen zu begreifen (vgl. etwa Audenaert & Furuta, 2010;Stone, 1982;Toms & O'Brien, 2008). Auch Wilson (2000) argumentiert, dass ein "total view of the information user" schwierig ist und jegliche partielle Blickwinkel genaue Definitionen der jeweiligen Ausschnitte erfordern.…”
Section: Tool Science and User Interface Designunclassified
“…Stone, in her 1982 study of the "information needs and uses" of humanities scholars, found this assumption to be provable. 15 She also discovered that "having retrospective coverage may be more important to the humanist than having access to current material." 16 Watson-Boone updated Stone's study in 1993 and created a composite portrait of the typical humanities scholar, using a combination of meta-analysis and interview techniques.…”
Section: Literature Reviewmentioning
confidence: 99%